ANALISIS E – SERVICE QUALITY PADA APLIKASI STUDENT ADMISSION SMB TELKOM UNIVERSITY - Sijabat, Astriyani; Widaningsih , Sri; Mustikasari, Ati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Telkom University is the best private university with the No.1 ranking in Indonesia which has changed the entire process of accepting prospective students using technology that is currently developing. The number of registrants that continues to increase in each year of admission makes Telkom University innovate to simplify the registration process for prospective students by creating a website-based application called